The Validity of the Image Processing Method by CASA in Hilal Observation - Unggul Suryo Ardi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2018)
Using of telescopes for the observing crescent often finds difficulties and failures. The combination of telescopes, digital cameras, and image processing methods through computerized processes is a good solution in the success of capturing the image of the new moon. The study related to the characteristics of the image processing method on CASA is a form of further research on previous studies which are still limited to discussing the validity of the crescent results through image processing according to the scholars. This study aims to find differences between the CASA and BMKG image processing methods, and test the validity of the CASA image processing method. This type of research is field research, by using data analysis techniques, descriptive analysis and comparative analysis. This study found that the CASA image processing method has differences with the BMKG image processing method. Processing the crescent image in both through the same software, namely IRIS. But the method used is different, because the first data collection is different. After processing the CASA image processing image crescent has a quality that is equally good compared to BMKG, the validity of the CASA image results.